GE_GERICHTE P/5370/2024 vom 21. Oktober 2024 - GE Cour de justice (2024)
ORDONNANCE PÉNALE;OPPOSITION TARDIVE;DÉLAI;CONDITION DE RECEVABILITÉ;QUALITÉ POUR AGIR ET RECOURIR;LÉSÉ | CPP.356; CPP.354; CPP.87; CPP.110; CPP.393.al1.letb; CPP.382; Cst.29.al2